The relationship between prolactin and adipose tissue and metabolic parameters in patients with polycystic ovary syndrome - Adanas, Gültekin; Turan Özsoy, Hilal Gülsm (The European Research Journal, 2020)
Objectives: Polycystic ovary syndrome is a reproductive endocrinopathy, predominantly accompanied by insulin resistance, obesity, and metabolic disorder. In this study, we aimed to investigate the possible relationship between prolactin and adipose tissue and metabolic parameters in patients with polycystic ovary syndrome (PCOS). Methods: A total of 58 patients with PCOS and 34 body mass index (BMI)-matched healthy controls between September 2018 and March 2019 were included in the study. Visceral and subcutaneous adipose tissues were measured using ultrasonography. Serum prolactin, fasting blood glucose, insulin, low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), triglyceride, total cholesterol, luteinizing hormone (LH), total testosterone, dehydroepiandrosterone sulfate (DHEA-S), and 17-hydroxyprogesterone (17-OHP) levels were measured. Results: The median BMI (p = 0.001), waist circumference (p = 0.002), hip circumference (p = 0.003), waist-to-hip ratio (p = 0.013), LH (p = 0.012), total testosterone (p = 0.004), DHEA-S (p = 0.049), 17-OHP (p = 0.001), insulin (p = 0.001), minimum preperitoneal fat thickness (p = 0.001), maximum preperitoneal fat thickness (p = 0.048), and intraperitoneal fat thickness (p = 0.018) were significantly higher in the PCOS group compared to the control group. However, there was no significant correlation between prolactin levels and adipose tissue parameters and insulin levels in the patients with PCOS. Conclusions: Although there was an increase in the preperitoneal and intraperitoneal fat thickness in the PCOS group compared to the control group, no significant correlation was observed between prolactin and visceral and subcutaneous adipose tissues and metabolic parameters.